Implementasi Surat Keterangan Tidak Dipungut Atas Impor Kapal (Implementation of Certificate Not Collected on Ship Import) - Sidabalok, Rodo Gokmatua; Wijaya, Suparna (STIE Malangkucecwara, 2021)
This study aims to analize the factors that affect the profitability of banks at state-owned banks and private foreign exchange banks listed on the IDX in 2015-2019. The factors used are liquidity, capital, credit risk, and operational efficiency. The analysis technique used is panel data regression with the Fixed Effect Model approach. The results showed that simultaneously liquidity, capital, credit risk and operational efficiency had a significant effect on profitability. then partially liquidity and capital do not have a significant effect on profitability, while credit risk and operational efficiency have a significant effect on profitability.